Membrane fractionation of gelatins extracted from skin of yellowfin tuna (Thunnus albacares): effect on molecular sizes and gelling properties of fractions - Montero Barrantes, Manuel (2022)
Membrane separation technologies allow the implementation of environmentally friendly and cost-effective processes to separate fine particles and molecules. Fractionation process of proteins from tuna skin gelatin was performed in four consecutive filtration steps using four membranes with pore diameters of 800 nm, 100 nm, 50 nm, and 20 nm. The retentates obtained from all membranes exhibited a similar protein size distribution. Gel strength and gelling and melting temperatures did not differ significantly among the tuna skin gelatin and the four retentates (p > .05). The permeate from the 20 nm pore diameter membrane exhibited significantly lower gelling properties than the other fractions (p < .05). The retentates of the four membranes presented gel strength values between 228 and 440 g. Gelling and melting temperatures from retentates and tuna skin gelatin ranged from 10.0 to 13.4°C and 18.0 to 20.6°C, respectively.